If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 = 7 + 4x Solving -25 = 7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -25 + -4x = 7 + 4x + -4x Combine like terms: 4x + -4x = 0 -25 + -4x = 7 + 0 -25 + -4x = 7 Add '25' to each side of the equation. -25 + 25 + -4x = 7 + 25 Combine like terms: -25 + 25 = 0 0 + -4x = 7 + 25 -4x = 7 + 25 Combine like terms: 7 + 25 = 32 -4x = 32 Divide each side by '-4'. x = -8 Simplifying x = -8
| 5(2x-31)+3=10x-155 | | 6(x-8)-3x=5(x-1)-1 | | 3+5-6+2x=-4(x-3)+7 | | -9(4x-2)=108-6x | | 4(2x+2)=7x+1 | | 6x+3x-x=96 | | 2c-11c+5=0 | | 2(m-3)=2(m-6) | | 5x^2-30x+100=0 | | 4(-5-x)=10-2x | | -.25x-9=.90 | | 8-h=-4 | | .28=.04(w-1.0) | | -4-6x=20 | | .28=.04(w-10) | | (3x^3)-(2x^2)= | | 0.4x-3.4=46 | | -.25-9=.90 | | 2x+11=3x+4 | | 3x^3-2x^2= | | -6m+69-9(m+1)=4m-(2m-2)-7m+6 | | 1170=68 | | (X^2+x-6)(x^2+x-2)+3= | | 0.50h-7=15 | | 9f+5(-8+3f)= | | 2[t-(2t+18)+15]=2(t+3) | | 4x+235=12x-5 | | (k,k+14)=0 | | 7y+8=1 | | 4m=12 | | 0.65x+.05(8-x)=.10(76) | | -28p-6(3-6p)=6(p-4)-2 |